The Yamato 980459 olivine-phyric shergottite consortium - Misawa, Keiji (National Institute of Polar Research, 2004)
P(論文) Among 4100 meteorite samples found around the Yamato Mountain area during the field season of 1998-1999, Yamato (Y) 980459, weight of 82g, is identified as a new shergottite. In ordered to improve our knowledge of the shergottite parent body, possibly Mars, a coordinated consortium study of the Y980459 shergottite was organized. Petrological, mineralogical, chemical and isotopic studies revealed that Y980459 is related to the olivine-phyric shergottites and the most primitive Martian basalt so far reported. Y980459 has solidified much faster than other shergottites, as indicated by its lack of plagioclase or maskelynite. Y980459 shows a light REE depleted pattern similar to other depleted shergottites" Dhofar 019, Dal al Gani (DaG) 476, Sayh al Uhamir (SaU) 005 and Queen Alexandra Range 94201. The Sm-Nd isotopic data suggest that Y980459 crystallized at 470Ma and derived from a highly depleted source region. Cosmic-ray exposure age of Y980459 is calculated to be 1Ma based on 10Be concentration, which is similar to those of olivine-phyric shergottites DaG 476 and SaU 005. I here present an outline of the consortium and implications for Martian geological history on the basis of ongoing studies. The first petrographical description of Y980459 by Ansgar Greshake, Jorg Fritz and Dieter Stoffler was not submitted to Antarctic Meteorite Research, but to Geochimica et Cosmochimica Acta on August 15, 2003, and was published in the May 15, 2004 issue. The other papers concerning Y980459 appeared in the Antarctic Meteorite Research, 17 issue are of equal scientific importance and priority. departmental bulletin paper